Service request management system application development with rapid application development method using web-based bubble sort algorithm - FX. Kristianto; Verdi Yasin; Anton Zulkarnain Sianipar; Rachmawaty Haroen; Yusra Fernando (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The Helpdesk system is a system to facilitate the reporting of technological information damage. Helpdesk systems are already widely used or developed somewhere with a wide variety of technologies and systems. Monitoring system as a process to collect data from various sources and helpdesk as the implementer of the monitoring system is required to be active to monitor reports from users. The helpdesk is a center point where problems or issues are reported in a coordinated and coordinated manner. The helpdesk is a complementary part of a function, service, and is responsible for problem solving. This is one of the obstacles in the implementation of work is still found errors in the process of handling remote hands or trouble shoot reports daily, weekly and monthly. Because currently the data and problem handling reports are still manual so it is difficult to see the status of handling. Helpdesk design system at PT. TH Indoplantations is a system where to facilitate users or customers and the Helpdesk data center division in processing a technical problem that occurs in the data center or customer or user devices located in the data center PT. TH Indoplantations. Based on the concept and design of a web-based helpdesk system at PT. TH Indoplantations can help in dealing with interference that occurs in customer devices.